The Determinants And Impact Of Access To Agricultural Credit On Productivity By Farmers In Nigeria; Evidence from Oyo State, Nigeria. - Samson, Ajayi; Obademi, Olalekan (Advances in Social Sciences Research Journal, 2018)
The focus of this study is to examine the determinants as well as impact of agricultural credit accessed by farmers in Oyo State on productivity, using Ibarapa region as a case study. Descriptive statistics, Probit model and Regression analysis as estimation techniques were used and data were sourced through structured questionnaire. The results obtained from the probit model shows that the model is well fitted for the analysis by revealing the factors that influence farmers’ access to Microfinance bank loan while the results obtained from the regression model revealed that the independent variables engaged in the equation for crop enterprise namely, farm size, labor cost, cost of seeds and amount of credit obtained have positive impact on productivity. Also, Chow-test result shows that the output of Microfinance bank credit beneficiaries is significantly different from that of non-beneficiaries of Microfinance bank credit. Based on the findings, it is recommended that savings mobilization by the Microfinance banks should be encouraged, and long loan repayment period of about two years coupled with low interest rate of at most 5% should be pursued. In addition, farmers should be insured against losses and microfinance bank credit programme should be gender sensitive as women have been reported to be equally efficient in farming activities like their men counterparts. Finally, Microfinance bank should inculcate into their credit programme, input availability (fertilizer, seed, medication etc) which will to a great extent increase agricultural productivity.